A study of etiology and epidemiology of onychomycosis from a tertiary care hospital in North India - Tyagi, Shivani; ., Neha; Kaur, Ravinder; Rawat, Deepti (International Journal of Research in Medical Sciences, 2021)
Background: Onychomycosis is the fungal infection of nail of which the incidence varies from 0.5-12% in India and around 5% worldwide.Onychomycosis is considered to be gender and age-related disease, being commoner in males and older adults in both genders. Apart from dermatophytes, other fungal agents like yeasts and non-dermatophyte moulds are increasingly being acknowledged as important etiological agents for the same. Our aim was to study the etiology of the nail infections in patients presenting to a dermatology department in a tertiary care hospital in central Delhi. Methods: This study included nail samples from patients of various age groups with suspected onychomycosis attending dermatology clinics in our hospital over a period of 2 years. For all samples, KOH wet mount microscopic examination followed by culture on Sabouraud’s dextrose agar was done. Growth of filamentous fungi and yeast obtained on SDA were identified using conventional microbiology techniques. Statistical analysis was performed using Epitools. Results: Of the total 1061 nail samples received, maximum prevalence seen in patients of age group 21 to 50 years. The positivity of onychomycosis was 57.02%. Out of culture positive samples, 24.62% grew dermatophytes and 75.37% grew non-dermatophytes (31.40% yeasts and 43.97% non-dermatophyte moulds). Trichophyton mentagrophytes was the most common (59.73%) dermatophyte followed by T. rubrum (23.49%) while among non-dermatophyte moulds; Aspergillus niger (20.68%) was the most common followed by A. flavus (16.54%) and others. Common yeasts included Candida spp. (65.79%) and Trichosporon spp. (28.95%). Conclusions: Non- dermatophytes are emerging as major etiological agents of onychomycosis which may be accounted various host factors. So, it becomes important to correctly identify the causative fungi to ensure appropriate treatment.